Kajian ke atas faktor daya tarikan pusat membeli-belah dalam mempengaruhi pengguna memilih pusat membeli-belah - Khairul Anuar Mohd Ali,; Juliana Ong Poh Ling, (Penerbit ukm, 2010)

(untitled)
The objective of the study is to identify features of a mall which make it attractive for shopping. Three shopping malls in Klang Valley had been chosen, which are Suria KLCC at Kuala Lumpur, Mid Valley Megamall at Petaling Jaya and Berjaya Times Square at Bukit Bintang. This study try to identify the factors of mall attractiveness that will influence consumer intention in choosing a shopping mall. Apart from that, this study also determines the factors that influence decision-making among respondents based on gender, age, ethnic, marriage status, education level and monthly income. The finding shows that the entertainment and variety are the main factors that influence consumer in choosing a shopping mall. The finding also indicates that there is no significant difference between male and female, age, education level and monthly income among the respondents. Meanwhile, there are significant differences in factors of mall attractiveness that influence the respondents based on ethnics and maritial status